Development Strategies of Camping Ground as a Nature-based Tourism Destination in Cihunjuran Mandalawangi, Pandeglang - Siti Nurkomala; Suci Sandi Wachyuni; FX Setiyo Wibowo (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This research aims to formulate a strategy for developing a camping ground as a nature-based tourism destination in Cihunjuran, Mandalawangi, Pandeglang Regency, Banten Province. Research method: The research used a mixed-method approach that combined qualitative and quantitative methodologies. The SWOT analysis and Quantitative Strategic Planning Matrix (QSPM) were employed to identify optimal development strategies. Data collection involved field observations, literature reviews, and in-depth interviews with camping ground managers, local government officials, visitors, and community members. Results and discussion: The results identified two factors (internal and external) that make the area potentially suitable for nature-based tourism. The internal factors consisted of strengths, like pristine natural beauty, diversity of flora and fauna, and affordable access, and weaknesses, such as inadequate infrastructure, lack of supporting facilities, and suboptimal promotion. Meanwhile, external factors include opportunities in the form of back-to-nature tourism trends, government support, and potential cooperation with local MSMEs and threats, such as competition with similar tourist destinations, environmental damage, and climate change. Based on the QSPM analysis, the most appropriate development strategy is an integrated tourism product development strategy with the highest TAS score (6.58). It was followed by a brand awareness strengthening strategy (6.23), sustainable infrastructure development (5.89), and local community empowerment (5.47) for improvement. Implication: The implementation of these strategies is expected to make the Cihunjuran camping ground a leading sustainable nature tourism destination in Pandeglang Regency. The improvement of this area can provide economic benefits for the surrounding community and also for the local MSMEs.